„Humanae vitae” odpowiedzią na współczesne sporyfilozoficzno-teologiczne oraz przypomnieniem podstawowych prawdchrześcijańskiej wiary - Ryszard Moń (Warszawskie Studia Teologiczne)
These reflections concern the problems discussed in the Humanae Vitae encyclical against the background of contemporary discussions about ethical maximalism and minimalism, the universal nature of moral norms, the existence of inherently evil acts, the so-called fundamental option, the specific nature of Christian ethics. On this basis, the essay then discusses issues which, while being strictly theological, have their reference to secular life, namely to fatherhood and parenthood, as the most significant, though often disregarded, issues discussed in the encyclical, a reminder of the basic truths of faith. Unless they are accepted, all topics related to marital life remain suspended in a vacuum. The encyclical shows that life is a gift from God, and not the effect of biological processes. Naturally, the latter are very important, but not essential. It therefore makes some maximal statements, showing that only this way will people be able to prove themselves as rational beings, who are responsible for and who truly love each other, rather than beings who are content to settle for less – instant gratification of their own desires. It is therefore a gross oversimplification to focus on the “detail” of the permissibility of contraception, while disregarding that which truly demonstrates the importance of the problem